Benefits of a complex solution to the customer’s problem for RSC on the market with chemical products - Lošťáková, Hana; Pecinová, Zuzana (University of Pardubice, 2013)
On B2B markets, the strategy of a complex solution to the customers’ problem is a more and more effective way to creating superior customer value (SCV). It leads to building and developing stronger relationships with customers on the principle of mutual benefit aiming to achieve higher customer satisfaction and loyalty. It also leads to a growth in the company’s competitiveness on the market, enhanced interconnection between the company and its customers, often also these customers’ customers, and thus to higher effectiveness of the entrepreneurial activities. Mainly the company’s ability to be flexible in their offer plays an important role in strengthening the relationships with customers (SRC). The thing is to offer a sufficient range of products, high quality products and their accessories (packaging, marking, accompanying documentation, etc.), but also a desirable level of a comprehensive system of pre-sale, sale and after-sale services, providing a complex solution to the customers’ problem. This article presents the results of a primary quantitative research, which focused on mapping perception of the benefits of a complex solution to the customers’ problem in the form of a customized range of products and quality of the supplied products and services for SRC and increasing their loyalty to the company from the point of view of managers of the selected chemical strategic business units (SBU’s).